Typological Analysis Of Cultural Heritage Objects In Uzbekistan In Different Periods. - Ravshanov Sobir Аbdukarim oʼgʼli; Usmonov Farrux Farxod oʼgʼli (Genius Journals, 2024)
This article reveals the typological analysis, general connection, and development of historical architectural objects and archaeological monuments built in different periods, which distinguish them from other countries with many historical monuments built on the territory of Uzbekistan.
Keywords: Uzbekistan; Antique; Sopollitepa; Middle Ages